FREQUENCY CONTROL OF BELT CONVEYOR SPEED IN MANUFACTURING FOOD - Khaliljonov, Botirjon Kodirjon ugli (Educational Research in Universal Sciences, 2023)
The text describes a physical model of a belt conveyor with an advanced control system. It highlights features such as cargo positioning control, height monitoring, basket fullness control, and belt speed management. The system employs optical sensors and movement detectors to ensure precise and efficient operation. The comprehensive control strategy enhances the overall functionality of the conveyor, making it a sophisticated laboratory installation for studying and optimizing material transport processes.